A salinity‐tolerant japonica cultivar has Na+ exclusion mechanism at leaf sheaths through the function of a Na+ transporter OsHKT1;4 under salinity stress. (5th January 2018) - Wangsawang, T.; Chuamnakthong, S.; Kohnishi, E.; Sripichitt, P.; Sreewongchai, T.; Ueda, A.
Abstract: This study was designed to investigate differences in patterns of physiological responses to salinity stress among five japonica rice cultivars in comparison with FL478 as a salinity tolerance check. Five japonica cultivars were screened for salinity tolerance at seedling stage based on visual symptoms of salt injury index and physiological parameters including dry matter production, electrolyte leakage ratio and ion concentration. The results indicated that cultivars Ouukan383 and FL478 were relatively more salinity tolerant than other cultivars and that Kanniho was the most salinity‐sensitive cultivar. Ouukan383 showed higher leaf water content and lower electrolyte leakage ratio under salinity stress. Notably, under salinity stress, Na + concentration in the leaf blades was much lower in Ouukan383 than in FL478, but was much higher in Kanniho. To understand the basis for these differences, we studied transcript levels of the genes encoding Na + transport proteins in different tissues. In response to salinity stress, Ouukan383 had highly induced expression of the OsHKT1;4 gene in the leaf sheaths, corresponding to higher Na + accumulation in the leaf sheaths and lower Na + accumulation in the leaf blades. On the other hand, the sensitive cultivar, Kanniho, had highly induced expression of the OsSOS1 and OsNHX1 genes in the leaf blades, whose gene products are responsible for Na + efflux outside cells and Na + compartmentalization into vacuoles. Thus, the salinity‐tolerant and salinity‐sensitive cultivars differed in their responses to Na + fluxes in plant cells using different transport systems in each tissue type. The salinity‐tolerant japonica cultivar, Ouukan383, has an effective Na + exclusion mechanism at the leaf sheaths to prevent Na + accumulation in the leaf blades. Such a mechanism, in combination with other genetic traits (e.g. Na + exclusion at the roots mediated by OsHKT1;5), offers the potential to improve salinity tolerance in rice.